PEMBERDAYAAN MASYARAKAT PESISIR MELALUI PENGEMBANGAN EKONOMI MARITIM DAN INOVASI OLAHAN PERIKANAN DI DESA JATIREJO KECAMATAN LEKOK KABUPATEN PASURUAN - Ernawati Ernawati; Romi Damar ZM; Yeni Lita Sari; Fayi Risma Mufidah; Riristiari Azzahrah Putri; Wahyu Intan Lestari; Muhammad Farid Hamka; Fitriya Hari; Sulistyawati Sulistyawati; Ferdiansyah Jodis Syaputra (Universitas Mataram, 2026)
Jatirejo Village, Lekok District, Pasuruan Regency, is a coastal area with abundant marine resource potential, particularly in the capture fisheries and aquaculture sectors. However, this potential has not been optimally utilized due to limited knowledge, skills in seafood processing, and market access. Furthermore, the stunting rate in this area remains high, reaching 23.8% in 2024. This activity aims to examine strategies for empowering coastal communities through integrated maritime economic development, including outreach and outreach at integrated health service posts (Posyandu) on stunting, training in fishery product processing innovations, product branding, and digital marketing. The methods used included field observations, in-depth interviews, and focus group discussions. The results indicate that the MSME empowerment program, through training in seafood processing, the production of healthy food products such as milkfish dim sum and fish bone sticks, as well as support for legality and digital marketing, has had a positive impact on the Jatirejo Village community, improving community skills, and opening up new, sustainable business opportunities. The initiative to register MSMEs on e-commerce platforms (Shopee), obtain Business Identification Numbers (NIB), and develop product identities through logos and packaging are strategic steps in expanding market reach. The management of MSMEs by PKK cadres and promotion by Karang Taruna youth demonstrates strong collaboration between community elements in implementing and maintaining the program's sustainability.